2015
DOI: 10.3109/09637486.2015.1088822
|View full text |Cite
|
Sign up to set email alerts
|

Co-ingestion of essence of chicken to moderate glycaemic response of bread

Abstract: Essence of chicken (EOC) beverage is a chicken meat extract, widely consumed in Asian countries for health benefits. EOC is a rich source of peptides and amino acids. White bread has become a popular staple food in all regions of Southeast Asia. A randomized controlled, crossover, non-blind trial was performed to investigate the role of EOC on glycaemic response (GR) of white bread. Ten healthy young subjects returned on five separate days for three glucose and two bread sessions. Subjects consumed bread or br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…Its uses include improving physical qualities of athletes, providing nutrition for recovering patients and restoring strength to women following childbirth [ 1 ]. Scientifically, beneficial effects of EC on physical health in thermic response [ 2 ], resting metabolic rate [ 3 ], reduction in blood glucose levels and glycemic response [ 4 , 5 ], colostrum composition [ 6 ] and recovery from physical exhaustion [ 7 ] have been demonstrated in human clinical studies. Beneficial effects on mental health include reduced anxiety [ 8 , 9 ], reduced depression [ 8 , 10 ] and improved general mental health [ 11 ] in normal or stressed healthy adults, as well as patients diagnosed with anxiety disorder [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Its uses include improving physical qualities of athletes, providing nutrition for recovering patients and restoring strength to women following childbirth [ 1 ]. Scientifically, beneficial effects of EC on physical health in thermic response [ 2 ], resting metabolic rate [ 3 ], reduction in blood glucose levels and glycemic response [ 4 , 5 ], colostrum composition [ 6 ] and recovery from physical exhaustion [ 7 ] have been demonstrated in human clinical studies. Beneficial effects on mental health include reduced anxiety [ 8 , 9 ], reduced depression [ 8 , 10 ] and improved general mental health [ 11 ] in normal or stressed healthy adults, as well as patients diagnosed with anxiety disorder [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Amino acids have been shown to stimulate gut peptides like glucagon-like peptide-1 (GLP-1), cholecystokinin (CCK) and peptide tyrosine tyrosine (PYY), and GLP-1, in particular, can increase early-phase insulin secretion [ 36 , 37 ]. Increased insulin has been found by our lab after ingestion of soymilk and amino acids from chicken essence [ 10 , 24 , 38 ]. In contrast, in this study, no increased insulin response was observed over two hours after the consumption of the soymilks as compared to the control.…”
Section: Discussionmentioning
confidence: 99%
“…There has been a long debate on the timing at which EOC should be consumed for maximum health benefits. One study showed that the coingestion of EOC with white bread was a simple strategy to reduce the glycaemic response of bread 79 . More interestingly, the same group found that the ingestion of EOC 15 min prior to the consumption of white rice elicited the greatest reduction in glycaemia 80 .…”
Section: Timing Fat and Protein Foods To Lower Glycaemic Response Of mentioning
confidence: 99%
“…Healthy Essence of chicken co-ingested with white bread reduced GR compared with white bread alone 79 Soong et al 80…”
Section: Menmentioning
confidence: 99%